Cellular integrative immune markers in elite athletes - Zacher, J.; Wesemann, F.; Joisten, N.; Walzik, D.; Bloch, W.; Predel, G. (International Journal of Sports Medicine, 2023)
The integrative immune markers neutrophil-lymphocyte-ratio (NLR), platelet-lymphocyte-ratio (PLR) and systemic immune inflammation index (SII) are established markers in clinical patient care. Adoption of these markers in elite athletics might prove beneficial for monitoring training and health. Blood samples of 195 healthy national Olympic squad athletes were collected before a graded bicycle-ergometric exercise test until complete exhaustion. Measurements included white blood cells, lymphocytes and platelets, allowing for the calculation of the integrative immune markers. Correlations between athlete characteristics (sex, age, sporting discipline, training experience, training volume) and integrative immune marker-values were assessed. In a subgroup analysis a second blood sample was collected from 25 athletes at 1 minute after exercise test to assess its effect on the immune marker levels.